(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
In contentious matters, some explicit provisions of the Protocol to the African Charter on Human and Peoples’ Rights on the Establishment of an African Court on Human and Peoples’ Rights and the Rules of Procedure of the Court define the procedural preconditions for submitting an application before the Court. These provisions also set out the essential criteria for intervention in a pending case. In the implementation of the right to submit an application and intervention, the concept of legal interest comes into play. With the aim of strengthening the position of the drafters of the African Court’s Protocol and the Rules of the Court, and to compensate for the imperfections of the observations of certain states, this contribution discussesthe concept of legal interest. It argues that legal interest is immaterial to the submission of application before the Court. However, during proceedings, the participation certain parties is subjected to their demonstrating they have legal interest. The rigid application of the concept of legal interest may be a hindrance nonetheless to the participation of a category of parties. Although the Court’s jurisprudence demonstrates the Court’s willingness to ensure broader participation in proceedings, the current state of scholarship does not sufficiently highlight this particularity of the African Court on Human and Peoples’ Rights system.